1962
DOI: 10.1017/s0021859600010121
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of Hyparrhenia veld for the nutrition of cattle in the dry season III. Studies on the digestibility of the produce of mature veld and veld hay, and the effect of feeding supplementary protein and urea

Abstract: Indigenous (Bos indicus) oxen fed ad lib. were used to measure the changes in the apparent digestibility of mature Hyparrhenia veld during the dry season, and also the apparent digestibility of late-cut veld hay and nitrogen-fertilized veld hay. The forages were those used in a field trial, and the present results complement previous work.1. Mature Hyparrhenia veld harvested at the end of the rains as veld hay or green forage, contains approximately 50% digestible o.m. and 0·6% digestible c.p. The low level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

1967
1967
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 9 publications
0
10
1
Order By: Relevance
“…The provision of supplementary protein has been shown to improve the utilization of low-quality roughage in many experiments such as those reported by Franklin, Briggs and McClymont (1955) in Australia, by Smith (1962) in Central Africa and by Raleigh and Wallace (1963) in the United States. These authors used roughages of 1-9, 3-6 and 5-5% CP respectively.…”
Section: The Data On Voluntary Intake Inmentioning
confidence: 89%
“…The provision of supplementary protein has been shown to improve the utilization of low-quality roughage in many experiments such as those reported by Franklin, Briggs and McClymont (1955) in Australia, by Smith (1962) in Central Africa and by Raleigh and Wallace (1963) in the United States. These authors used roughages of 1-9, 3-6 and 5-5% CP respectively.…”
Section: The Data On Voluntary Intake Inmentioning
confidence: 89%
“…There are only a few data in the literature on cattle receiving such low-quality tropical herbage. Smith (26) found that cattle weighing approximately 1000 Ib ate only 12 Ib or less DM per day, which was considerably below their maintenance requirements. Marshall and Bredon (16) in an evaluation of mature Themeda triandra measured intakes by steers (of about 600 Ib) and found them to be J to | of maintenance needs.…”
Section: S0 Imentioning
confidence: 98%
“…The means ranged from 3-90±0-76 kg to 4-62 + 1-30 kg/head/day for stall-fed steers, while for the grazing animals it ranged from 5-67 + 1-35 in treatment H to 6-59 + 1-08 kg/head/day in treatment K. Smith (1962) using East African Zebu and Sanga oxen reported a range in D.M. intake of 3-8-8-6 kg/head/day (live weight range of 376-V. A. OYENUGA AND F. 0.…”
Section: Discussionmentioning
confidence: 85%
“…Reid et al (1973) reported a range of 42-9-74-0 % for dry-matter digestibility of six tropical grass species in Uganda using sheep; Johnson et al (1967) gave the mean dry-matter digestibility for P. maximum using Holstein cows and water buffaloes in the Philippines as 55-3 and 59-4 % respectively, while Smith (1962) in Rhodesia gave a range of 37-8-50-3% for the OM digestibility of mature Hyparrhenia veld (standing) hay and 60-6% for the late-cut hay of the same grass species previously treated with nitrogen fertilizer, using East African Zebu and Sanga oxen. Similar and lower digestibility values have been reported by other workers for some tropical and subtropical grass and legume species (Elliot & Croft, 1958;Elliot & Fokkema, 1960;Milford, 1957Milford, , 1960Topps, 1962;Minson, 1971;Cowlishaw & Archibald, 1972).…”
Section: Discussionmentioning
confidence: 99%